Socially Responsible Indexes and Non-financial Disclosures. The Case Study of the WIG-ESG - Ciesielski, Krzysztof (Indeksy społecznie odpowiedzialne a ujawnienia niefinansowe na przykładzie WIG-ESG, 2024)
The aim of the study was to answer the question of how being listed on the WIG-ESG index affects the quality of published non-financial information. The author studied the annual reports of companies listed on the WIG-ESG, and of companies outside this index. The analysis of variance and grouping using the k-means method, followed by the evaluation of the obtained division by the value of the silhouette index, showed that in terms of the variables describing the quality of published non-financial information, it was impossible to demonstrate that companies listed on the WIG-ESG stand out when compared to other entities.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 2, s. 74-94
Keywords: non-financial reporting; socially responsible indexes; WIG-ESG; Warsaw Stock Exchange; raportowanie niefinansowe; indeks odpowiedzialny społecznie; Giełda Papierów Wartościowych w Warszawie